An entropic regularization method for solving systems of fuzzy linear inequalities - F. B. Liu (International Journal of Mathematics and Mathematical Sciences)
Solving systems of fuzzy linear inequalities could lead to the solutions of fuzzy linear programs. It is shown that a system of fuzzy linear inequalities can be converted to a regular min-max problem. An entropic regularization method is introduced for solving such a problem. Some computational results are included.